2019
DOI: 10.3390/catal9080684
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hydrothermal Stability in Glass Diesel Soot Oxidation Catalysts

Abstract: The hydrothermal stability of K-Ca-Si-O glass soot oxidation catalysts has been improved by substitution of Ce and Zr for Ca. This work demonstrates that glasses can be tailored to withstand the challenging diesel exhaust hydrothermal environment by considering the field strengths and partial molar free energies of the hydration reactions (ΔGi) of the cation species in the glass. The result is a glass that shows less formation of precipitates after 2 h hydrothermal exposure in air with 7% H2O at temperatures r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…For some catalysts (i.e., perovskites), a decrease in activity due to potassium loss was observed, ,, while for some active phases (i.e., potassium–TM mixed oxides, glasses), it remains nearly intact. ,,, It has been reported that the alkali precursors in particular counteranions play an important role in terms of activity and stability (KNO 3 > K 2 CO 3 ) . A promising method of alkali metal stabilization is their immobilization within an oxide matrix, by forming nanostructured phases or glasses, ,, which can be further optimized by adding other dopants …”
Section: Reactivity Of Alkali-containing Soot Combustion Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…For some catalysts (i.e., perovskites), a decrease in activity due to potassium loss was observed, ,, while for some active phases (i.e., potassium–TM mixed oxides, glasses), it remains nearly intact. ,,, It has been reported that the alkali precursors in particular counteranions play an important role in terms of activity and stability (KNO 3 > K 2 CO 3 ) . A promising method of alkali metal stabilization is their immobilization within an oxide matrix, by forming nanostructured phases or glasses, ,, which can be further optimized by adding other dopants …”
Section: Reactivity Of Alkali-containing Soot Combustion Catalystsmentioning
confidence: 99%
“…150 A promising method of alkali metal stabilization is their immobilization within an oxide matrix, by forming nanostructured phases 218 or glasses, 226,228,229 which can be further optimized by adding other dopants. 145 The stability of the soot combustion catalysts containing alkali promoters has been also investigated in the presence of contaminants such as SO 2 74,81,252,254 or water vapor. 252,254 Alkali-modified perovskites exhibit good resistance to both sulfur and water, 252 while potassium-promoted ceria shows low resistance to sulfur and water at high temperatures.…”
Section: Monolithic Catalystsmentioning
confidence: 99%
“…The use of alcohol−water solutions for the impregnation of cobalt had positive effects, since smaller particles with a high dispersion on the ceramic fibers were obtained, differently than when pure water was utilized. Temperature-programmed oxidation (TPO) results have shown that the catalysts prepared by using alcohol solvents had the best catalytic performance in terms of soot conversion as well as of maximum rate for soot combustion (at about Zokoe et al investigated the possibility of improving K-Ca-Si-O glass soot oxidation catalysts with higher hydrothermal stability in a diesel exhaust environment [53]. The authors used Zr and Ce for substituting Ca in a K-Ca-Si-O glass, obtaining a more hydrothermal resistant catalyst.…”
Section: Carrier Structurementioning
confidence: 99%
“…In particular, the authors used different Ce/Zr ratios in the range of 1/9-1/1 and studied morphology, phase structure, and physicochemical properties of the obtained fibers. The results have shown that the sample CZ-2-700 Zokoe et al investigated the possibility of improving K-Ca-Si-O glass soot oxidation catalysts with higher hydrothermal stability in a diesel exhaust environment [53]. The authors used Zr and Ce for substituting Ca in a K-Ca-Si-O glass, obtaining a more hydrothermal resistant catalyst.…”
Section: Carrier Structurementioning
confidence: 99%
See 1 more Smart Citation